2014
DOI: 10.1038/nrm3741
|View full text |Cite
|
Sign up to set email alerts
|

Regulated protein turnover: snapshots of the proteasome in action

Abstract: The ubiquitin-proteasome system (UPS) is the main ATP-dependent protein degradation pathway in the cytosol and nucleus of eukaryotic cells. At its centre is the 26S proteasome, which degrades regulatory proteins and mis-folded or damaged proteins. In a major breakthrough, several groups have determined high-resolution structures of the entire 26S proteasome particle in different nucleotide conditions and with and without substrate using cryo-electron microscopy combined with other techniques. These structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
224
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(228 citation statements)
references
References 179 publications
(258 reference statements)
3
224
0
1
Order By: Relevance
“…It is postulated that cleavage may cause conformational change of the TDP-43-C, which enables it for direct and quick access to the chamber of the 20S proteasome. 43 As TDP-43-C contains a portion of the glycinerich region that is required for its interaction with other hnRNPs, and for the regulation of alternative splicing and transcriptional activity, 12 we propose that rapid removal of TDP-43-C contributes to the loss-of-function of TDP-43 following CVB3 infection. In addition to loss-of-function, our results also suggest a gain-of-toxic-function for TDP-43-N. We demonstrated that expression of TDP-43-N in HeLa cells, which contain abundant endogenous TDP-43, results in a significant reduction of CFTR splicing, indicating that TDP-43-N inhibits the biological functions of native TDP-43 as a dominantnegative mutant.…”
Section: Discussionmentioning
confidence: 92%
“…It is postulated that cleavage may cause conformational change of the TDP-43-C, which enables it for direct and quick access to the chamber of the 20S proteasome. 43 As TDP-43-C contains a portion of the glycinerich region that is required for its interaction with other hnRNPs, and for the regulation of alternative splicing and transcriptional activity, 12 we propose that rapid removal of TDP-43-C contributes to the loss-of-function of TDP-43 following CVB3 infection. In addition to loss-of-function, our results also suggest a gain-of-toxic-function for TDP-43-N. We demonstrated that expression of TDP-43-N in HeLa cells, which contain abundant endogenous TDP-43, results in a significant reduction of CFTR splicing, indicating that TDP-43-N inhibits the biological functions of native TDP-43 as a dominantnegative mutant.…”
Section: Discussionmentioning
confidence: 92%
“…The 19S regulatory particle (~900 kDa) binds and unfolds the ubiquitinated substrates, and the 20S proteolytic core (~700 kDa) is responsible for the hydrolysis of the substrate proteins. 31,32 The 19S particle, attached at either or both ends of the 20S particle, consists of two sub-complexes, the base and the lid. The base is composed of six ATPases (regulatory particle triple A proteins RPT1-RPT6), two large organizing subunits (regulatory particle nonATPases 1 [RPN1] and 2 [RPN2]), and two ubiquitin receptors (RPN10 and RPN13).…”
Section: Congenital Malformationsmentioning
confidence: 99%
“…The base is composed of six ATPases (regulatory particle triple A proteins RPT1-RPT6), two large organizing subunits (regulatory particle nonATPases 1 [RPN1] and 2 [RPN2]), and two ubiquitin receptors (RPN10 and RPN13). 1,[31][32][33][34] The lid is formed from the deubiquitylating enzyme RPN11 and eight non-ATPase subunits (RPN3, RPN5-RPN9, RPN12, and RPN15), containing the PCI (proteasome-CSN [COP9 signalosome]-eIF3 [eukaryotic translation initiation factor 3]) domains. 1,[31][32][33][34] Whereas the base acts as a reverse chaperone, unfolding and translocating substrate proteins into the 20S cavity, the lid ensures substrate recognition, deubiquitination, and scaffolding.…”
Section: Congenital Malformationsmentioning
confidence: 99%
See 2 more Smart Citations